Genre Based Approach to Teaching Multimodal Text - Rahmadhani, Astuti Pratiwi (Jurnal Curricula, 2018)
The study reports on the analysis of the using multimodal text, especially photographs, in teaching writing recount text in genre-based approach classroom. The study employed a qualitative research design, embracing the characteristics of a case study. The data were obtained from several sources including classroom observations, and students’ texts. The analysis reveals that despite the limitation, the teaching program is successful. The students are able to develop the activities in Background Knowledge of Study (BKOF), Modelling of Text (MOT), Joint Construction of the Text (JCOT), and Independent Construction of the Text (ICOT). The students show positive response to improve their writing ability. The data from observation reveals that the students can follow the activities in the teaching program. The students are able to handle the instruction given by the teacher and discuss them with their classmates. The teacher as the participant observer can bravely describe that the students enjoy the activities and have good enthusiasms to involve in each activity. The analyses show that the students have many progressions toward the implementation of the teaching program. The progressions are observed before the implementation, during, and final writing in the teaching program. Based on the results, the students can develop their ability in terms of the writing concepts. The data support the assumption that multimodal texts help the students to understand and construct the text in a good way.